VENTILATION SYSTEMS IN BRAZILIAN POULTRY: STATE OF THE ART - Vilela, M. O.; Gates, R. S.; Souza, C. F.; Martins, M. A.; Tinôco, I. F. F.; Teles Júnior, C. G. S. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Brazil is one of the main world producers of chicken meat and eggs, and in order to remain competitive, new methodologies have been studied and implemented with the purpose of obtaining greater production yield, always emphasizing management, diet, sanitation and environment. In this sense, the monitoring and control of variables related to the indoor thermal environment and air quality are extremely important. Furthermore, the current consumer profile is increasingly demanding a focus on animal welfare and origin of products consumed are fundamental criteria for decision making at the purchase time. In commercial poultry production, one of the crucial needs is to guarantee a comfortable environment for the birds and, consequently, proper ventilation system design. To achieve the best distribution of air flow in poultry facilities and, thus, to meet international welfare and air quality requirements, according to the required quality standards, this literature review aimed provides a survey of the main ventilation systems and their applicability to Brazilian poultry production.